1996
DOI: 10.1074/jbc.271.50.32241
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function of Pancreatic β-Cell Delayed Rectifier K+ Channels

Abstract: Voltage-dependent delayed rectifier K؉ channels regulate aspects of both stimulus-secretion and excitationcontraction coupling, but assigning specific roles to these channels has proved problematic. Using transgenically derived insulinoma cells (␤TC3-neo) and ␤-cells purified from rodent pancreatic islets of Langerhans, we studied the expression and role of delayed rectifiers in glucose-stimulated insulin secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
134
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(142 citation statements)
references
References 36 publications
6
134
2
Order By: Relevance
“…This would be similar to the well-known effect of inhibiting beta cell Kv currents on insulin secretion, even with very high concentrations (20 mmol/l) of TEA [11,16,20]. We found that alpha cell Kv currents are inhibited by low millimolar levels of TEA and 4-aminopyridine.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This would be similar to the well-known effect of inhibiting beta cell Kv currents on insulin secretion, even with very high concentrations (20 mmol/l) of TEA [11,16,20]. We found that alpha cell Kv currents are inhibited by low millimolar levels of TEA and 4-aminopyridine.…”
Section: Discussionsupporting
confidence: 87%
“…Notably, we did not observe the TEA-resistant rapidly inactivating current component reported previously in isolated alpha cells [19] and alpha cells from intact islets [3]. In beta cells, inhibition of Kv currents with TEA augments insulin secretion in a glucose-dependent manner, since Kv channels contribute to action potential repolarisation [11,16,20]. Since alpha cells are electrically active at low glucose [3,4,21], we hypothesised that inhibition of Kv currents at low glucose concentrations should enhance glucagon secretion under this condition, due to action potential prolongation as is the case for beta cell insulin secretion.…”
Section: Methodsmentioning
confidence: 44%
See 1 more Smart Citation
“…A summary of expression the various K v families in insulinoma cells and rat islets has been compiled by . In the resting β cell the K v channels are closed and they open in response to membrane depolarization following glucose-induced insulin secretion (Roe et al, 1996). In relation to insulin secretion the effects of the K v2.1 channel has been the one most studied in cellular models as it possibly is the major contributor to the voltagedependent outward K + current.…”
Section: Potassium Channelsmentioning
confidence: 99%
“…Changes in the relative concentrations of the metabolites ATP and ADP cause ␤-cell depolarization via closure of ATP-sensitive potassium channels (K ATP ), 3 which results in activation of voltage-operated Ca 2ϩ channels, Ca 2ϩ influx, and insulin secretion (1). The extent of ␤-cell depolarization and insulin release are regulated in part by the activation of repolarizing ion channels, including the voltage-gated potassium channel, Kv2.1 (2)(3)(4). One mechanism employed by pancreatic ␤-cells to regulate the biophysical activity of the ion channels involved in insulin release involves hydrolysis of membrane phospholipids to yield mediators that include inositol triphosphates and free fatty acids (5)(6)(7)(8).…”
mentioning
confidence: 99%